SISTEM PENDUKUNG KEPUTUSAN KELOMPOK EVALUASI INFRASTRUKTUR JALAN RAYA TERHADAP KEMACETAN LALU LINTAS MENGGUNAKAN METODE TOPSIS DAN BORDA (Studi kasus pada Jalan di Pulau Lombok) - , I Made Purwantara, Dr. Azhari SN., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Lombok, as the region that depend on tourism as the biggest income areas, need well-organized public transportation to support the development of Lombokâs island. Therefore, it need a good highway infrastructure which clear from the traffic problems. So that, the main roads which has high traffic have to evaluated. Input from the road user needed to know the traffic problems. This is done in order that the highway inspector know and can anticipate traffic congestion problems on thatâs roads. The road inspectors will seeking fot the alternative solution that be accepted by groups. The application of group decision support system (GDSS) that made using Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method can help the decision maker in ranking the value of each alternative solution, because this method based on concept that the choosen alternative not only has the shortest way from positive ideal solution, but also has the longest from the negative ideal solution. Meanwhile, Borda method as one of voting method which in its application will counting back the result that produced by the decision makers, by give weight to each alternative based on their rank. The highest weight value is a collective decision from the decision makers. The result of this study showed that the system that has been built has a capability to support the decision makers in evaluate highway infrastructure in Lombok and decided alternative solution that can choose to anticipate the traffic congestion problems.